ESTIMATION OF ERROR FOLLOWED BY KNOWLEDGE OF RESULTS IN A MODERATE OR HIGH FREQUENCY ENHANCES MOTOR LEARNING AND MAY AVOID EXTRINSIC FEEDBACK DEPENDENCE - Fabiano de Souza Fonseca; Lucas Savassi Figueiredo; Marilya Andrade da Silva Lima; Jaime da Silva Souza Maciel; Drumond Gilo da Silva; João Vitor Alves Pereira Fialho (Journal of Physical Education)
ABSTRACT The present study aimed to analyze how different schedules combining error estimation and relative frequency of extrinsic feedback affects motor learning. Fifty-two undergraduate students (30 males, 22 females) aged 18 to 35 years old (M = 21.15, SD = 2.97), all novices in the task, practiced a force-production task with different combinations between error estimation and relative frequency of knowledge of results. Four experimental conditions were compared: no error estimation with feedback after every trial; no error estimation with feedback every two trials; error estimation following by feedback after every trial-and-error estimation following feedback every two trials. The absolute force error analysis revealed a significant main effect for both feedback frequency [F(1, 76) = 4.209, p = 0.044, ηp 2 = 0.52] and error estimation [F(1, 76) = 7.483, p = 0.008, ηp 2 = 0.77]. The constant force error analysis did not reveal a significant main effect for Error Estimation [F(1, 76) = 2.323, p = 0.132, ηp 2 = 0.37], but did for Feedback Frequency [F(1, 76) = 8.481, p = 0.005, ηp 2 = 0.83]. Results showed superior learning of groups that combined error estimation following receiving feedback, regardless of feedback frequency. The association between error estimation and relative frequency of extrinsic feedback (high or moderate) seems to favor the development of error-detection mechanism, thus avoiding the effects of extrinsic feedback dependence, and consequently enhancing learning